2015
DOI: 10.1038/srep15531
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis, expression profiles and function of thioredoxin 2 and thioredoxin reductase 1 in resistance to nucleopolyhedrovirus in Helicoverpa armigera

Abstract: The thioredoxin system, including NADPH, thioredoxin (Trx), and thioredoxin reductase (TrxR), plays significant roles in maintaining intracellular redox homeostasis and protecting organisms against oxidative damage. In this study, the characteristics and functions of H. armigera HaTrx2 and HaTrxR1 were identified. Sequence analysis showed that HaTrx2 and HaTrxR1 were both highly conserved and shared high sequence identity with other insect counterparts. The mRNA of HaTrx2 was expressed the highest in 5th insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…The dithiol moieties of Trx1 are reduced by receiving electrons from NADPH in the presence of TrxR15. Reduced Trx1 in turn reduces downstream proteins and plays vital roles in regulating cellular redox state, inhibiting apoptosis and increasing the resistance of cancer cells to cytotoxic drugs67. Nevertheless, when Trx1 becomes over-oxidized, the cellular conditions may become more sensitive to oxidative stress and more inclined to apoptosis8.…”
mentioning
confidence: 99%
“…The dithiol moieties of Trx1 are reduced by receiving electrons from NADPH in the presence of TrxR15. Reduced Trx1 in turn reduces downstream proteins and plays vital roles in regulating cellular redox state, inhibiting apoptosis and increasing the resistance of cancer cells to cytotoxic drugs67. Nevertheless, when Trx1 becomes over-oxidized, the cellular conditions may become more sensitive to oxidative stress and more inclined to apoptosis8.…”
mentioning
confidence: 99%
“…Our transcriptional analysis revealed that the GmTrx2 and GmTrx-like1 were expressed at higher levels in the head and salivary glands than other larval tissues. In other insects, BmTrx exhibited higher expression in the fat body and silk gland ( Kim et al, 2007 ); AccTrx1 was mainly expressed in the epidermis ( Yao et al, 2014 ); HaTrx2 gene was expressed at higher levels in the head and epidermis ( Zhang et al, 2015 ). It revealed that the expression of Trx exhibits a tissue-specific pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The AccTrx1 and AccTrx2 from A. cerana cerana were upregulated by low or high temperatures, H 2 O 2 , and pesticides (acaricide, paraquat, cyhalothrin, and phoxime) treatments ( Yao et al, 2013 , 2014 ). In H. armigera , the transcript of HaTrx2 was significantly stimulated by low or high temperatures, UV light, mechanical injury, microorganism [ E. coli , M. anisopliae , and nucleopolyhedrovirus (NPV)] ( Zhang et al, 2015 ). In this study, GmTrx2 and GmTrx-like1 were obviously induced by 15 and 35°C, E. coli , M. anisopliae , H 2 O 2 , and pesticides-emamectin benzoate treatments, suggesting that GmTrx2 and GmTrx-like1 may play critical roles in resisting oxidative stress caused by these adverse conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mock‐infected larvae were fed with an equal amount of sterile water (0 OBs/ml) on artificial diet. Larvae were reared individually in a single glass tube, and after 48 hr, untreated diet was replenished as needed (Zhang, Li et al., ).…”
Section: Methodsmentioning
confidence: 99%